Perencanaan Anggaran di dalam Suatu Lembaga Pendidikan Islam - Saidah, Siti; Suraijiah, Suraijiah (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
Budget planning is a crucial aspect of managing educational institutions, including Islamic educational institutions. A budget serves not only as an operational tool to sustain institutional activities but also as a strategic guideline for achieving educational objectives, such as improving the quality of learning, developing facilities, and enhancing the welfare of educators. This study aims to analyze the concept of effective budget planning in Islamic educational institutions, focusing on budgeting principles, implementation strategies, and solutions to address common challenges.This research employs a library research method, drawing on books, journal articles, and relevant official documents. The findings reveal that effective budget planning involves comprehensive needs identification, prioritizing fund allocation, and periodic evaluations to ensure optimal budget utilization. Key principles such as transparency, efficiency, accountability, and stakeholder participation are identified as critical elements in budget planning for Islamic educational institutions. Nevertheless, Islamic educational institutions often face challenges such as limited funding, dependency on external sources, and a lack of professional financial management systems. This study highlights the importance of developing alternative funding sources, such as waqf funds, and integrating information technology to enhance accountability and transparency. With well-structured budget planning based on sound financial management principles, Islamic educational institutions can effectively support the achievement of their educational goals.